Rumen Microbiology: From Evolution to Revolution 2015
DOI: 10.1007/978-81-322-2401-3_12
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Feed Additives

Abstract: The recent global concerns associated with the use of antibiotics and other growth-promoting stimulants in the animal feeds have created a window of opportunities and responsibilities for livestock nutritionists to search for alternative safer feed additives, such as direct-fed microbials based on viable naturally occurring benefi cial microorganisms. In the last decade, nutritionists and microbiologists have elucidated comprehensive details related to the normal intestinal microbiota of mammals and also the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…A wide range of feed additives has been studied and applied for rumen fermentation manipulation in sheep production [3,4,5,6]. In addition to directly providing nutrients, such as rumen-protected lysine, the supplementation of microbial additives and antibiotics has been the major nutritional approach to altering rumen function and animal performance [7,8]. However, microbial additives are normally unstable in their quality and consequently in the response of animal performance [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide range of feed additives has been studied and applied for rumen fermentation manipulation in sheep production [3,4,5,6]. In addition to directly providing nutrients, such as rumen-protected lysine, the supplementation of microbial additives and antibiotics has been the major nutritional approach to altering rumen function and animal performance [7,8]. However, microbial additives are normally unstable in their quality and consequently in the response of animal performance [7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to directly providing nutrients, such as rumen-protected lysine, the supplementation of microbial additives and antibiotics has been the major nutritional approach to altering rumen function and animal performance [7,8]. However, microbial additives are normally unstable in their quality and consequently in the response of animal performance [7]. Antibiotics, such as monesin, have been banned in some countries due to concerns over the formation of antibiotic-resistant microbial mutants [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Robertson et al (2015) measured the GHG emission from the cradle to the farm gate for fat and protein-corrected goat milk and found that the carbon footprint was between 0.84 and 1.03 kg CO 2 -eq. On the other hand, several previous studies have focused on mitigation strategies such as feeding strategies, benefiting rumen modifiers, and selecting the appropriate animal breed for reducing enteric methane and GHG emissions (Dohme et al, 2000;Bhatta et al, 2009;Patra and Saxena, 2010;Ripoll-Bosch et al, 2013;Nagpal et al, 2015;Vagnoni et al, 2015). However, all previous studies ignored the effects of the management system of the goat farm.…”
Section: Introductionmentioning
confidence: 99%
“…(Oboh 2006;Ubalua 2007), Trichoderma viride (Ezekiel et al 2010), Aspergillus niger and Saccharomyces cerevisiae (Iyayi and Losel 2001), Rhizopus oligosporus and Aspergillus niger (Kolapo et al 2021), and Rhizopus oryzae (Vlavonou 1988) resulted in a product with higher protein content, lower cyanogenic glycosides and phytate content. In addition, the inclusion of microorganisms with probiotic potentials to the animal diet is known to promote growth and enhance the performance of livestock (Nagpal et al 2015;Arowolo and He 2018). In this regard, some yeasts, such as Saccharomyces cerevisiae (Alizadeh et al 2016), selenium yeast and Phaffia rhodozyma yeast (Shurson 2018) have shown remarkable usefulness.…”
Section: Introductionmentioning
confidence: 99%